Lateritic soil stabilization by using roadpacker plus - Li Lian, Goh (2014)
In Malaysia, more than half the area in Peninsular Malaysia is covered with lateritic soil. Improvement method is needed to provide a strong subgrade construction during construction process. Currently, there are a lot of popular improvement methods and stabilization methods are used in the field. In study, 7% and 13% of RoadPacker Plus were used as a mean of stabilization treatment of soil while 0% act as control sample. Soil stabilization is the alteration of one or more soil properties, by mechanical or chemical means, to improve soil material possessing the desired engineering properties. The main purpose of soil stabilization is to increase soil strength, bearing capacity and resistance to deteriorative forces of nature and manmade environment. Laboratory tests were conducted to determine the engineering properties of soil sample such as classification, Standard Proctor Compaction Test, and Unconfined Compressive Test (UCT). For compaction test, 7% RoadPacker Plus content has the highest MDD value which is 1.54 with 25.47% of moisture content. As for the UCS testing, soil mixture with 7% RoadPacker Plus content have gain higher strength improvement as compare to 13% content. The results indicated that RoadPacker Plus is able to significantly improve the unconfined compression strength of Laterite soil. The soil strength increased with the duration of curing period. As a result, RoadPacker Plus is suitable to use for some practical project such as increasing road bearing capacity.